Analisis Pengukuran Antropometri Dan Tingkat Kesegaran Jasmani: Studi Survei Pada Tim Bola Voli Putra - Rosalina, Rosi; Janah, Roudhotul; Hartanto, Hartanto (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. The purpose of this study was to determine the level of physical fitness and anthropometric conditions of male athletes in Volleyball. Materials and methods. This study used a descriptive form survey with an observational approach method and analysed using quantitative descriptive statistics. The population in this study amounted to 12 male Volleyball athletes, the variables studied were anthropometric measurements and physical fitness levels. Result. The results of the study with a total sample of 12 male Volleyball athletes showed the results of anthropometric measurements dominant in the moderate category, namely 52%. In the physical fitness level test the dominant in the good category is 50%. In the anthropometric test the athletes who won the 1st mayor cup of Probolinggo city on average were in the moderate category while in the physical fitness level test the athletes who won the 1st mayor cup of probolinggo city had an average in the good category. The data collected is primary data through the measurement of the Indonesian Physical Fitness Test (TKJI) and anthropometry. Anthropometric characteristics of respondents in the form of Body Weight (BB), Height (TB) and also the age of the respondent. Cunclotion. The implementation of anthropometric analysis and physical fitness tests can help or play an important role in evaluating the condition of athletes for achievement to a higher level. With the analysis of anthropometric measurements and physical fitness levels, it is hoped that it can be used as a reference for coaches or trainers in knowing which athletes have superior quality so that they can provide maximum coaching and athletes can contribute better achievements in the national and international arena.